Analysis of the prevalence of pediculosis and scabies in orphanages and refugee shelters in south-eastern Poland - Andrzej Tytuła; Katarzyna Bartosik; Anita Jasztal-Kniażuk; Weronika Buczek; Aleksandra Błaszkiewicz; Agnieszka Borzęcka-Sapko (Kazimierz Wielki University, 2019)
Grouping conditions refer to a situation when number of entities is considered as a unit. The members of such a community resides in a certain area at a specified time and has to comply with specific rules of social life. The analysis of the data from orphanages and refugee shelters in south-eastern Poland has confirmed that this type of living conditions promote transmission of scabies and pediculosis, and these diseases were most frequently diagnosed in young people taking active part in social life. Our study revealed that invasions of Pediculus humanus and Sarcoptes scabiei are still current public health threats although the obligation to report cases of these diseases in Poland has been abolished.